Alterations in Knee Kinematics After Partial Medial Meniscectomy Are Activity Dependent. (June 2015) - Edd, Shannon N.; Netravali, Nathan A.; Favre, Julien; Giori, Nicholas J.; Andriacchi, Thomas P.
Background: Alterations in knee kinematics after partial meniscectomy have been linked to the increased risk of osteoarthritis in this population. Understanding differences in kinematics during static versus dynamic activities of increased demand can provide important information regarding the possible underlying mechanisms of these alterations. Hypothesis: Differences in the following 2 kinematics measures will increase with activity demand: (1) the offset toward external tibial rotation for the meniscectomized limb compared with the contralateral limb during stance and (2) the difference in knee flexion angle at initial foot contact between the meniscectomized and contralateral limbs. Study Design: Controlled laboratory study. Methods: This study compared side-to-side differences in knee flexion and rotation angles during static and dynamic activities. Thirteen patients (2 female) were tested in a motion capture laboratory at 6 ± 2 months after unilateral, arthroscopic, partial medial meniscectomy during a static reference pose and during 3 dynamic activities: walking, stair ascent, and stair descent. Results: The meniscectomized limb demonstrated more external tibial rotation compared with the contralateral limb during dynamic activities, and there was a trend that this offset increased with activity demand (repeated-measures analysis of variance [ANOVA] for activity, P = .07; mean limb difference: static pose, –0.1° ± 3.3°, P = .5; walking, 1.2° ± 3.8°, P = .1; stair ascent, 2.0° ± 3.2°, P = .02; stair descent, 3.0° ± 3.5°, P = .005). Similarly, the meniscectomized knee was more flexed at initial contact than the contralateral limb during dynamic activities (repeated-measures ANOVA for activity P = .006; mean limb difference: reference pose, 1.0° ± 2.5°, P = .09; walking, 2.0° ± 3.9°, P = .05; stair ascent, 5.9° ± 5.3°, P = .009; stair descent, 3.5° ± 4.0°, P = .004). Conclusion: These results suggest both a structural element and a potential muscular element for the differences in kinematics after partial medial meniscectomy and highlight the importance of challenging the knee with activities of increased demands to detect differences in kinematics from the contralateral limb. Clinical Relevance: With further investigation, these findings could help guide clinical rehabilitation of patients with torn meniscus tissue, especially in the context of the patients' increased risk of joint degeneration.